The N-terminal of NBPF15 causes multiple types of aggregates and mediates phase transition. Issue 2 (31st January 2020) - Wu, Han; Zhai, Liu-Tao; Guo, Xue-Xue; Rety, Stephane; Xi, Xu-Guang
Abstract : The neuroblastoma breakpoint family ( NBPF ) consists of 24 members that play an important role in neuroblastoma and other cancers. NBPF is an evolutionarily recent gene family that encodes several repeats of Olduvai domain and an abundant N-terminal region. The function and biochemical properties of both Olduvai domain and the N-terminal region remain enigmatic. Human NBPF15 encodes a 670 AA protein consisting of six clades of Olduvai domains. In this study, we synthesized and expressed full-length NBPF15, and purified a range of NBPF15 truncations which were analyzed using dynamic light scattering (DLS), superdex200 (S200), small-angle X-ray scattering (SAXS), far-UV circular dichroism (CD) spectroscopy, transmission electron microscope (TEM), and crystallography. We found that proteins containing both the N-terminal region and Olduvai domain are heterogeneous with multiple types of aggregates, and some of them underwent a liquid-to-solid phase transition, probably because of the entanglement within the N-terminal coiled-coil. Proteins that contain only the Olduvai domain are homogeneous extended monomers, and those with the conserved clade 1 (CON1) have manifested a tendency to crystallize. We suggest that the entanglements between the mosaic disorder-ordered segments in NBPF15 N terminus have triggered the multiple types of aggregates and phase transition of NBPF15 proteins, which could be associated with Olduvai-related cognitive dysfunction diseases.